2018
DOI: 10.1038/s41418-018-0248-7
|View full text |Cite
|
Sign up to set email alerts
|

The proneural gene ASCL1 governs the transcriptional subgroup affiliation in glioblastoma stem cells by directly repressing the mesenchymal gene NDRG1

Abstract: Achaete-scute homolog 1 gene (ASCL1) is a gene classifier for the proneural (PN) transcriptional subgroup of glioblastoma (GBM) that has a relevant role in the neuronal-like differentiation of GBM cancer stem cells (CSCs) through the activation of a PN gene signature. Besides prototypical ASCL1 PN target genes, the molecular effectors mediating ASCL1 function in regulating GBM differentiation and, most relevantly, subgroup specification are currently unknown. Here we report that ASCL1 not only promotes the acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Moreover, the finding of Barrett and colleagues (20) that Id1 hi cells initiate tumors containing both Id1 hi and Olig2 + cells, whereas tumors from Id1 lo /Olig2 − cells do not generate Id1 hi progeny, is consistent with our transcriptomic and genetic lineage tracing in human specimens. More recently, Narayanan and colleagues showed that ASCL1 is a master regulator of the proneural phenotype of GBM, and that ASCL1 directly represses mesenchymal-phenotype genes such as CD44 and GFAP (21). This is consistent with our data; in particular, our scATAC-seq analysis shows anticorrelation of CD44 and other mesenchymal genes with ASCL1 gene-body activity and motif enrichment ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the finding of Barrett and colleagues (20) that Id1 hi cells initiate tumors containing both Id1 hi and Olig2 + cells, whereas tumors from Id1 lo /Olig2 − cells do not generate Id1 hi progeny, is consistent with our transcriptomic and genetic lineage tracing in human specimens. More recently, Narayanan and colleagues showed that ASCL1 is a master regulator of the proneural phenotype of GBM, and that ASCL1 directly represses mesenchymal-phenotype genes such as CD44 and GFAP (21). This is consistent with our data; in particular, our scATAC-seq analysis shows anticorrelation of CD44 and other mesenchymal genes with ASCL1 gene-body activity and motif enrichment ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…MYBL2 is a member of the MYB family of transcription factors that plays important roles in cell cycle progression and maintenance of cells in an undifferentiated state (Musa et al, 2017). Its functions oppose that of ASCL1-a transcription factor promoting neuronal differentiation-and putatively crucial to maintaining the Proneural transcription landscape (Narayanan et al, 2019), which is consistent with the observation that overexpression of ASCL1 in vitro (Narayanan et al, 2019) and knockdown of MYBL2 in silico (this paper) are detrimental to Proneural subtype cells. Additionally, the fact that the subtype-specific essential TF MYBL2 is also implied to be functional interaction partners with the corresponding subtype's signature TFs further supports the idea that our signature analyses are capable of capturing GBM subtype-specific biology.…”
Section: Discussionsupporting
confidence: 87%
“…al. reported that ASCL1 not only promotes the acquisition of a proneural phenotype in glioblastoma cells but also represses mesenchymal features 39 . A similar relationship may exist in neuroblastoma cells, in which the more neural crest-like mesenchymal cells do not express ASCL1 , and ASCL1 expression is specifically upregulated as cells differentiate along the sympathetic lineage and express members of the ADRN CRC.…”
Section: Discussionmentioning
confidence: 99%